Effect of autoclaving on the formation of resistant starch from two Nigeria Cassava (Manihot esculenta) varieties - Abioye, V.F.; Adeyemi, I.A.; Akinwande, B.A.; Kulakow, Peter A.; Maziya-Dixon, B.B. (Rynnye Lyan Resources, 2018)
This study evaluated the effect of autoclaving process on the production of resistant starch (RS) from cassava starch. RS was prepared by debranching, autoclaving and storage of cassava starch from two Nigeria varieties (TMS 30572 and TMS 98/0581). Starch suspensions were prepared with different starch water ratios (1:1; 1:3; and 1:5), debranched with isoamylase, autoclaved at 110 and 121◦C for four heat and cool cycles, stored under refrigeration and freezing condition for 48 h. Debranching process increased RS by about 73-78%. Higher RS was obtained at higher temperature and with significant difference (p<0.05) from each other. RS increased with storage time from 6.23 to 9.60 and 22.40 to 25.77 g/100 g for undebranched and debranched samples, respectively, after 48 h. This study indicated the potentials of these Nigeria cassava varieties in the production of RS which could serve as functional food.